Three Cases of Aphasic Status Epilepticus: Clinical and Electrographic Characteristics - Lee, Jung-Ju (Clin Med Insights Case Rep, 2021)
Aphasic status epilepticus (ASE) is unusual and has clinical characteristics similar to those of other disorders. Herein, we report 3 cases of ASE. A left-handed man (patient 1) showed continuous aphasia after the administration of flumazenil. He had underlying alcoholic liver cirrhosis and traumatic brain lesions in the right hemisphere. Electroencephalography (EEG) revealed periodic epileptiform discharges in the right frontotemporal area, which were intervened by rhythmic activity with spatiotemporal evolutions. A right-handed woman (patient 2) showed recurrent aphasia. Blood tests revealed a high blood glucose level (546 mg/dL) and high serum osmolality (309 mMol/L). Her EEG showed rhythmic activity in the left frontotemporal area with spatiotemporal evolutions on a normal background rhythm. She became seizure-free after the administration of an antiepileptic drug and strict glucose regulation. A right-handed woman (patient 3) developed subacute aphasia a week before hospital admission. She had a gradual decline of cognition 1 year before. Her EEG showed intermittent quasi-rhythmic fast activity in the frontotemporal area bilaterally, with fluctuating frequency and amplitude. The patient became seizure-free after the administration of an antiepileptic drug. Brain single-photon emission tomography performed after seizure control showed decreased perfusion in the left frontotemporal area. After discharge, her cognitive function gradually declined to a severe state of dementia. ASE can be caused by diverse etiologies; it is usually caused by cerebral lesions and less frequently by non-lesional etiologies or degenerative disorders. Adequate treatment of underlying disorders and seizures is critical for curing the symptoms of ASE.